2021
DOI: 10.1097/md.0000000000025411
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of biomarkers in the diagnosis of acute kidney injury secondary to liver cirrhosis

Abstract: This study is to investigate the role of neutrophil gelatinase-associated lipocalin (NGAL), cystatin C (CysC) and creatinine in the diagnosis of acute kidney injury (AKI) secondary to liver cirrhosis. A total of 825 patients (including 540 liver cirrhosis patients and 285 healthy controls) were enrolled. Liver cirrhosis patients were further subdivided into AKI secondary to liver cirrhosis group (AKI group, 210 patients) and simple liver cirrhosis group (LC group, 330 patients). Serum NGAL/urine NGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The proposed mechanism is that damaged renal tubular cells lead to the upregulation of NAGL expression [38]. Urine and serum NGAL are independent predictors of AKI, with a higher sensitivity and specificity of uNGAL [39]. Some older studies showed that urinary levels of NAGL are correlated with the degree of renal injury, the value being markedly increased in urinary tract infections and acute tubular necrosis (ATN) compared to those with prerenal azotemia due to renal depletion, hepatorenal syndrome, or chronic kidney disease [40].…”
Section: Urinary Biomarkersmentioning
confidence: 99%
“…The proposed mechanism is that damaged renal tubular cells lead to the upregulation of NAGL expression [38]. Urine and serum NGAL are independent predictors of AKI, with a higher sensitivity and specificity of uNGAL [39]. Some older studies showed that urinary levels of NAGL are correlated with the degree of renal injury, the value being markedly increased in urinary tract infections and acute tubular necrosis (ATN) compared to those with prerenal azotemia due to renal depletion, hepatorenal syndrome, or chronic kidney disease [40].…”
Section: Urinary Biomarkersmentioning
confidence: 99%
“…These tests may help identify AKI earlier compared to sCr and are promising; however, they are not widely available, and none of them are specific [ 3 , 11 , 32 , 33 ]. The majority of the studies comparing ATN vs. other etiologies lack histological confirmation of ATN.…”
Section: Diagnostic Workup Of Acute Kidney Injury In Patients With Ci...mentioning
confidence: 99%
“…Evaluation of renal function is usually done by measuring serum Cr in order to assess the GFR [5]. However, in patients with cirrhosis, serum Cr measurements are often inaccurate and often lie within the normal range due to factors such as age, gender, inadequate nutrition, muscle atrophy, bilirubin levels, renal tubular secretion malignancy or liver disease [3,6,7].…”
Section: Introductionmentioning
confidence: 99%